An integrated assessment of microfluidic microbial fuel cell subjected to vibration excitation. (15th April 2023) - Hu, Xiaoyi; Tan, Xinru; Shi, Xiaomin; Liu, Wenjun; Ouyang, Tiancheng
Abstract: Microfluidic microbial fuel cell is considered as a new development direction of green and sustainable energy systems. Compared with other microbial electrochemical reactors, microfluidic microbial fuel cells have lower cost and higher energy efficiency. In practice, vibration is a non-negligible factor affecting the performance of microfluidic microbial fuel cell. However, numerical studies in this area are lacking. In the current work, a two-dimensional transient model for microfluidic microbial fuel cell is established by coupling the vibration force field with hydrodynamics, mass transfer, whole-cell electrochemical reaction kinetics and microbial growth. The correctness of the model is guaranteed by comparing the experimental data with simulation results. After model validation, an integrated assessment of the vibration effect on microfluidic microbial fuel cell is obtained. Major conclusions show that vibration excitation can inhibit the growth of electricigens inside the anode, thus reducing the output performance of microfluidic microbial fuel cell. Increasing the vibration intensity and frequency will exacerbate this effect. However, appropriate vibration excitation is beneficial to the substrate removal of microfluidic microbial fuel cell. Vibration will destroy the laminar flow pattern in the microchannel and increase the bacteria concentration inside the cathode. Additionally, the increment of feed flow rate is conductive to enhancing the anti-vibration ability of the cell Graphical abstract: Highlights: The transient bi-population model for microfluidic microbial fuel cell is proposed. Uneven distributions of bacteria on both anode and cathode are revealed. Effects of vibration force on cell performance and bacteria distribution are studied. The anti-vibration abilities of microfluidic microbial fuel cells are evaluated.